ISLAMIC FAMILY LAW DURING THE REFORMATION PERIOD - Rizka, Jamilah; Arfa, Faisar Ananda; Turnip, Ibnu Radwan Siddiq (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study aims to explain the reform of Islamic family law and also explain the dynamics in the process of Islamic family law reform. Family law has an important position in Islam. Family law as the core of sharia. The research results show that the reform period opened up greater space for community participation in law formation, as well as strengthening the role of women in the discourse on family justice. This is related to the opinion of the Muslim community which sees Islamic family law as the initial entry point into the Islamic religion. This research aims to examine the dynamics and development of Islamic Family Law during the reform period, both from the aspects of legislation, institutions and social practices of Muslim communities. This study uses a library research method, namely a method used by studying, reviewing, and also examining library materials that have legal relevance to the subject of discussion. The data obtained in this study was analyzed descriptively using reduction, display and verification techniques. Islamic family law reform has become a discourse in the study of Islamic law. This discourse has become a phenomenon since the 20th century AD, this is evidenced by the increasing number of attempts to reform Islamic legal thought carried out by Muslim scholars, supported by the very complex conditions and development situations of the times.